EVALUASI PROGRAM PRAKTEK PENGALAMAN LAPANGAN (PPL) DAN KULIAH KERJA NYATA (KKN) TERPADU DI STKIP TAMAN SISWA BIMA - Deddy Meirawan; Abdul Rahman A. Ghani; Ernawat; Ika Irawati (Sekolah Pascasarjana Universitas Muhammadiyah Prof. DR. Hamka bekerjasama dengan Himpunan Evaluasi Pendidikan Indonesia (HEPI)., 2023)
Tujuan evaluasi ini adalah untuk mengevaluasi serta mendeskripsikan pencapaian program PPL-KKN terpadu yang dilaksanakan oleh STKIP Taman Siswa Bima. Evaluasi ini menggunakan model CIPP (Context, Input, Process, dan Product) serta menggunakan metode evaluatif yang bersifat deskriptif. Instrumen yang dipergunakan pada pengumpulan datanya adalah observasi, wawancara, serta dokumentasi. Hasil dari evaluasi konteks yang sesuai dengan kebutuhan stakeholder adalah: buku panduan belum ada, visi-misi hanya mengikuti visi-misi kampus, lingkungan KKN ditentukan terlebih dahulu, Hasil evaluasi produk PPL, ada peningkatan prestasi untuk siswa yang diajar, sedangkan output KKN, untuk tema literasi dan numerasi ada peningkatan prestasi dari siswa yang diajar, untuk tema kewirausahaan, mahasiswa sudah belajar menciptakan produk, dan untuk tema desa wisata, tempat rekreasinya sudah diperindah. The purpose of this study was to evaluate and describe the achievements of the integrated PPL-KKN program implemented by STKIP Taman Siswa Bima. This evaluation research used CIPP model (Context, Input, Process, and Product) and used descriptive qualitative methods. The instruments used in data collection are observation, documentation, and interviews. The results of the context evaluation which it suitable of stakeholder need, namely: that there are no guidebooks, the vision and mission only follow the campus visions and missions, the KKN environment is determined in advance, the main goal is to maximize the theme program, the requirements for joining PPL-KKN have been determined, and the main need is teaching science. The results of the evaluation of inputs for facilities and infrastructure are 80% feasible and 20% inadequate for PPL, while for KKN 95% are feasible, the budget is greatly minimized, 96% of human resources are met. The results of the evaluation process, reduced learning time while increasing student interest (PPL), literacy and numeracy processes were in line with expectations, entrepreneurship was constrained by student abilities, and tourist villages were constrained by cost, while only part of the village program was completed. The results of the PPL product evaluation, there is an increase product of students’ value, while the output of KKN, fir literacy and numeracy theme, there is an increase of students’ achievement being taught, for the theme of enterpreneurship, students’ had learnt to create the product, and for the theme of tourist village, the recreation area had been beautified.